PENGEMBANGAN BUKU KERJA MANDIRI BERBASIS STEM UNTUK SISWA SEKOLAH DASAR - Julia, Ranti; Sofwan, Muhammad; Risdalina, Risdalina (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research aims to design and develop a STEM-based Independent Workbook for Science and Social Studies (IPAS) learning for fourth-grade elementary school students. The development was driven by the limited availability of innovative instructional materials, variations in students’ learning abilities, and the insufficient integration of the STEM approach in IPAS instruction. The study applied a Research and Development (R&D) methodology using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The analysis phase revealed that students encountered difficulties in comprehending IPAS content when learning relied solely on textbooks and conventional worksheets. In response, the independent workbook was developed with contextual material presentation, engaging layouts, and a variety of exploratory activities, exercises, and STEM-oriented tasks aimed at fostering learner autonomy and critical thinking skills. Validation results indicated an average score of 3.36 from media experts (fairly valid), 4.16 from content experts (valid), and 4.92 from language experts (very valid). Practicality testing showed that teacher responses reached an average score of 4.45, categorized as very practical, while student responses in large-scale trials achieved an average score of 4.81, also classified as very practical. These findings suggest that the STEM-based Independent Workbook is appropriate for use as a supplementary learning resource in elementary IPAS instruction, as it effectively supports students’ independence, engagement, and conceptual understanding. ABSTRAKPenelitian ini berfokus pada pengembangan Buku Kerja Mandiri berbasis STEM yang digunakan dalam pembelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) bagi peserta didik kelas IV sekolah dasar. Pengembangan ini dilatarbelakangi oleh keterbatasan bahan ajar yang variatif dan inovatif, heterogenitas kemampuan belajar siswa, serta penerapan pendekatan STEM yang belum terintegrasi secara optimal dalam pembelajaran IPAS. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE yang mencakup tahap analisis, perancangan, pengembangan, penerapan, dan evaluasi. Hasil tahap analisis menunjukkan bahwa penggunaan buku paket dan LKS konvensional belum sepenuhnya membantu siswa dalam memahami materi IPAS. Oleh karena itu, buku kerja mandiri dirancang dengan tampilan yang menarik, materi kontekstual, serta dilengkapi aktivitas eksploratif, latihan, dan tugas berbasis STEM untuk menumbuhkan kemandirian belajar serta kemampuan berpikir kritis. Hasil validasi menunjukkan skor rata-rata sebesar 3,36 dari ahli media dengan kategori cukup valid, 4,16 dari ahli materi dengan kategori valid, dan 4,92 dari ahli bahasa dengan kategori sangat valid. Uji kepraktisan menunjukkan respon guru memperoleh skor rata-rata 4,45 dengan kategori sangat praktis, sedangkan respon siswa pada uji coba kelompok besar mencapai skor rata-rata 4,81 dengan kategori sangat praktis. Dengan demikian, buku kerja mandiri berbasis STEM dinyatakan layak digunakan sebagai bahan ajar pendukung pembelajaran IPAS di sekolah dasar karena mampu meningkatkan kemandirian, minat belajar, dan pemahaman siswa terhadap materi.